(untitled) (Quest Journal of Management and Social Sciences, 2020)
Background: Teachers are actors and thus play various roles and responsibilities in the classroom, school and entire community. Their commitment contributes to increasing the skills, knowledge, creativity, intelligence, devotion, and attitudes of the school community. The demographic heterogeneity of teachers affects not only performance but also thecommitment level of the school community. Objectives:The study aims to find the influence of socio-demographic variables on the organizational commitment of school teachers in Kathmandu and Lalitpur districts. Methods: This study is quantitative and based on primary data. The study has employed a conclusive research design. The population of the study was secondary level teachers in Kathmandu and Lalitpur districts, and a number of them were selected using the principles of purposive sampling. The size of the sample was 232. Results: The study reveals that affective, continuance, normative as well as overall commitment of teachers in school do not differs in terms of gender and education level. However, affective commitment increases as an increase in service years whereas continuance commitment increases at the beginning years of service for five years. However,between five to ten years, it lessens.Again after ten years, it increases if the teacher is involvedin the same job for one decade. Conclusions: The commitment of teachers is not affected by their gender and education level. However, the years in service spent by teachers influence their affective and continuance commitment but not the normative commitment. Implications: The findings of this study can be useful for school administrators and policymakers to find the influence of demographic factors on the commitment of school teachers.